1991
DOI: 10.1111/j.1600-0404.1991.tb04656.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum and CSF immunological findings in ALS

Abstract: Serum and CSF immunological findings were analysed in 37 patients with amyotrophic lateral sclerosis (ALS). ALS patients had significantly higher mean values of serum IgG and complement component C4 and significantly lower mean value of total haemolytic titre of complement (THC) compared with normal controls. Incidence of immune complexes (ICs) was significantly higher in sera of ALS patients than in normal controls. There was no significant difference regarding mean serum levels of IgM, IgA, and complement co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 15 publications
4
51
1
3
Order By: Relevance
“…Indeed, other studies have shown that many complement factors and their receptors can be synthesized by both neurons and glia in the CNS (17). Although there is breakdown of the blood-brain barrier in the end stages of ALS (34,35), the accumulating evidence for abundant local complement expression in many cell types in the CNS may indicate that this provides a local microenvironment for exacerbating ALS pathology compared with that provided by infiltration of systemic complement factors.…”
Section: Expression Of Complement Factors and Receptors For C5a Are Amentioning
confidence: 99%
“…Indeed, other studies have shown that many complement factors and their receptors can be synthesized by both neurons and glia in the CNS (17). Although there is breakdown of the blood-brain barrier in the end stages of ALS (34,35), the accumulating evidence for abundant local complement expression in many cell types in the CNS may indicate that this provides a local microenvironment for exacerbating ALS pathology compared with that provided by infiltration of systemic complement factors.…”
Section: Expression Of Complement Factors and Receptors For C5a Are Amentioning
confidence: 99%
“…The concept of BBB dysfunction in ALS is not new, and was suggested in a few human studies of spinal fluid characteristics that demonstrated an elevated CSF albumin/ serum albumin ratio in a large percentage of ALS patients (19,20). However, enthusiasm for treating ALS patients with APC might be dampened by several factors, including the disappointing experience of trying to translate therapeutic successes in mutant SOD1 animals to ALS patients (21).…”
Section: Limitations Of the Mouse Model Of Alsmentioning
confidence: 99%
“…suggesting local production in response to disturbance in CNS homeostasis due to immunoglobulin deposits and auto-antibodies in the CNS of ALS patients (Donnenfeld et al, 1984, Niebroj-Dobosz et al, 2006. Also the circulation could be a source of these complement factors as there is BBB breakdown in the end stages of ALS (Apostolski et al, 1991). Overall, evidence from these clinical studies helps us to propose that complement system activation occurs in ALS patients, and may play a role in the disease pathology.…”
Section: Clinical Evidence Of Complement Involvement In Alsmentioning
confidence: 89%
“…Subsequent studies measured C3c, C4, C1 inactivator and C3 activator fractions in the serum and CSF of 13 ALS patients but only detected increased levels of C3c in the CSF of ALS patients compared to normal individuals (Annunziata and Volpi, 1985). Furthermore Apopstolski and colleagues (1991) measured serum C4, C3 and Factor B levels in 33 ALS patients and found an increase in C4 levels when compared to normal individuals (Apostolski et al, 1991). Increased clusters of C3d and C4d coated fibers on oligodendroglia and degenerating neurites in spinal cord and motor cortex was also found in 8 ALS patients compared to 5 normal individuals (Kawamata et al, 1992).…”
Section: Clinical Evidence Of Complement Involvement In Alsmentioning
confidence: 99%
See 1 more Smart Citation